El tejido de la brisa : nuevos asedios a la obra de Marvel Moreno y Germán Espinosa - Illán Bacca, Ramón, 1938- (Universidad del Norte Editorial, 2017)
This book examines the narrative works of writers Marvel Moreno and Germán Espinosa: their themes, forms and resources, in order to determine their inscription in the canon of Colombian and Latin American literature.